Management of Emergencies in the Hepato-Gastro-Enterology Department of the Kara University Hospital - Mouzou, E. T.; El-Hadji, Yakoubou R; Mategnan, P. (British Journal of Healthcare and Medical Research, 2025)
Introduction: Emergency care in hepato-gastroenterology (HGE) at CHU-Kara is expanding. Objective: To assess the management of emergencies in the general hospital ward at CHU-Kara. Materials and methods: This was a retrospective study of patient records from 1 January 2023 to 30 June 2024. It ran from July 1 to September 31, 2024. Results: 170 emergencies were identified, with a hospital frequency of 20.90% and a sex ratio of 1.6. The average age was 49 years. Digestive haemorrhage was the leading emergency (69.41%), dominated by ruptured oesophageal varices (RVO), followed by peptic ulcers. Other emergencies were hepatic encephalopathy (12.94%), acute abdominal pain (11.77%), ingestion of caustic products (2.94%) and chronic vomiting (2.94%). All patients had undergone an initial assessment combined with non-specific resuscitation. All patients had not undergone aetiological investigation. Vasoactive drugs in the splanchnic territory were not available. In addition to secondary prevention of RVR, their management was based on the administration of non-cardioselective beta-blockers used alone. The course of treatment was marked by a high mortality rate of 31.76%, due to the delay in consultation, the severity of the life-threatening condition, the patients' lack of financial resources, the absence of health insurance and the inadequacy of the technical facilities. Conclusion: Emergencies in the Emergency Department are frequent at CHU-Kara; they are dominated by upper digestive haemorrhage, which is life-threatening.